The startup way : - Ries, Eric (Curency, 2017)
Entrepreneur and bestselling author of The Lean Startup, Eric Ries reveals how entrepreneurial principles can be used by businesses of all kinds, ranging from established companies to early-stage startups, to grow revenues, drive innovation, and transform themselves into truly modern organizations, poised to take advantage of the enormous opportunities of the twenty-first century.